Pediatric Cryptococcal Lymphadenitis in the Absence of AIDS: Case Report and Literature Review. (4th June 2013) - Bao, Fengchang; Tan, Hongna; Liu, Wei; Li, Yange; Li, Huixia
Abstract : We present a rare case of cryptococcal lymphadenitis without immunocompromization in a two-and-a-half-year-old child. He was referred to our center with a fifteen-day history of continued fever. Ultrasound and computed tomography (CT) revealed the enlargement of multiple lymph nodes and lung reticulonodular shadows. Hematological, immunological, and microbiological tests for hepatitis, lymphoma, AIDS, and immunoglobulin deficiencies were negative. Laboratory tests demonstrated elevated erythrocyte sedimentation rate, elevated plasma and urinary ß2-microglobulin (ß2-MG) levels, and elevated C-reactive protein and fibrinogen. Both blood routine and bone marrow aspiration showed elevated eosinophil granulocytes. The diagnosis of cryptococcal lymphadenitis was obtained by excisional biopsy of the cervical lymph nodes. The patient was treated with intravenous amphotericin B and oral flucytosine for five weeks, then with subsequent oral fluconazole for three months. The patient is now doing well. Our case suggests that the diagnosis of cryptococcal lymphadenitis is very difficult without etiology and pathology, especially for a patient with a normal immune system; lymph node biopsy is necessary to diagnose it, and immediate antifungal treatment is necessary to treat it.